2494. Influenza B Hospitalizations Are Associated With Mortality in Children, FluSurv-NET, 2011–2017. (26th November 2018) - Garg, Shikha; O'Halloran, Alissa; Cummings, Charisse Nitura; Chai, Shua J; Alden, Nisha; Yousey-Hindes, Kimberly; Anderson, Evan J; Ryan, Patricia; Collins, James; Smelser, Chad; Blog, Debra; Felsen, Christina B; et al.
Abstract: Background: Influenza B viruses (B) co-circulate with influenza A viruses (A) and contribute to influenza-associated hospitalizations each season. We used data from the Influenza Hospitalization Surveillance Network (FluSurv-NET) to determine the association between B virus hospitalizations and mortality among children. Methods: We included data from children aged 0–17 years, residing in a FluSurv-NET catchment area, and hospitalized with laboratory-confirmed influenza during 2011–2012 through 2016–2017. We abstracted data on underlying conditions, clinical course and outcomes from medical charts. After excluding cases with unknown influenza type or with A/B coinfection, we compared characteristics of children hospitalized with A vs. B using univariate analyses and multivariable logistic regression, to determine the independent association between virus type and in-hospital mortality. Results: Among 7671 children hospitalized with influenza, 5607 (73%) had A and 2064 (27%) had B. The proportion of B hospitalizations varied by season from 11% during 2013–2014 to 42% during 2012–2013. Among children with B, median age was 4 years (interquartile range 1–8 years), 58% were male and 36% were non-Hispanic white. In univariate analysis, children with B were more likely to be older, have cardiovascular and neurologic disease, to be vaccinated (38 vs. 32%), and to be hospitalized ≥2 days after illness onset, and were less likely to have asthma and receive antivirals (71 vs. 79%) compared with those with A ( P < 0.05). There were no differences in the proportion with ≥1 underlying condition (59% both groups). Patients with B vs. A were no more likely to require intensive care (19 vs. 20%; p 0.34) or receive mechanical ventilation (6 vs. 5%; p 0.13); however, patients with B were more likely to die in-hospital (1 vs. 0.4%; P < 0.01). The unadjusted odds of in-hospital mortality for children with B vs. A was 2.3 (95% confidence interval (CI) 1.3–4.1), which remained elevated at 2.0 (95% CI 1.1–3.7) after adjusting for age, season and underlying conditions. Conclusion: Influenza B virus infections were associated with severe outcomes among hospitalized children. Although death was uncommon, children with B had twice the odds of dying in-hospital compared with those with A virus infection. Disclosures: E. J. Anderson, NovaVax: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant. AbbVie: Consultant, Consulting fee. MedImmune: Investigator, Research support. PaxVax: Investigator, Research support. Micron: Investigator, Research support. H. K. Talbot, Sanofi Pasteur: Investigator, Research grant. Gilead: Investigator, Research grant. MedImmune: Investigator, Research grant. Vaxinnate: Safety Board, none. Seqirus: Safety Board, none.